1999
DOI: 10.1016/s0022-2860(98)00654-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure elucidation and photochemistry of substituted carboxylic compounds by low temperature matrix-isolation and solid state vibrational spectroscopy

Abstract: Molecular structures and chemical reactivity (aggregation, phase transitions and photochemistry) of a series of substituted carboxylic acids were studied by low temperature matrix isolation and solid state vibrational spectroscopy, complemented by ab initio molecular orbital calculations. The conformational preferences exhibited by the isolated molecules of the systems under study are analyzed, and the effects of aggregation, temperature change and irradiation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…The mechanisms of the photolysis processes cannot be unequivocally established on the basis of the experiments here described. However the photochemical reactions shall involve radical intermediates resulting from a-cleavages either of the C-C a bond or C-O bond, as found previously for most of the carboxylic acids that undergo decarboxylation or decarbonylation reactions upon UV irradiation [31][32][33][34][35][36]. This indicates that the decomposition reactions shall take place mainly on the excited state surfaces rather than in the vibrationally excited ground state.…”
Section: Resultsmentioning
confidence: 56%
“…The mechanisms of the photolysis processes cannot be unequivocally established on the basis of the experiments here described. However the photochemical reactions shall involve radical intermediates resulting from a-cleavages either of the C-C a bond or C-O bond, as found previously for most of the carboxylic acids that undergo decarboxylation or decarbonylation reactions upon UV irradiation [31][32][33][34][35][36]. This indicates that the decomposition reactions shall take place mainly on the excited state surfaces rather than in the vibrationally excited ground state.…”
Section: Resultsmentioning
confidence: 56%
“…[10][11][12] Detailed structural and vibrational studies were reported for the monocarboxylic parent molecule, propenoic acid (acrylic acid, CH 2 dCHCOOH), 13 and the related molecules, (Z)-and (E)-3-methyl-propenoic [(Z)-and (E)-crotonic acid, CH 3 CHdCHCOOH]. 14,15 These studies revealed that these molecules exist both in the gas phase and in solid argon in two conformational states differing by internal rotation around the C R -C bond and having similar energies [∆E (s-trans)-(s-cis) ≈ 3 kJ mol -1 ]. The s-cis conformer (CdC R -CdO dihedral equals to 0°) was found to be the conformational ground state for the three molecules.…”
Section: Introductionmentioning
confidence: 99%
“…3,6 The individual molecules belong to the C 2 symmetry point group, with both carboxylic groups out of the plane of the carbon atoms adopting the cis arrangement around the C-O bond ( Figure 1). 7 Monomeric malonic acid and its monoanion have been studied previously by Hartree-Fock ab initio self-consistent field (SCF)-molecular orbital (MO) calculations using smallsize basis sets (STO-3G and 4-21G) in order to explain the large dissociation constant ratio k 1 /k 2 . This ratio is usually exhibited by dicarboxylic acids where the monoanion can be stabilized by intramolecular hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%